The Fragility of Plausibility Structures: Reconstructing the Social Foundation of Religious Moderation Policy in Indonesia - Luthfin Mahamida (CV Edujavare Publishing, 2026)
This article extends the author's previous research on the social construction of religious moderation in Indonesia by focusing on Peter L. Berger's concept of plausibility structures. Rather than revisiting the full dialectical framework of externalization, objectification, and internalization, it examines why religious moderation continues to experience a plausibility deficit despite its strong institutionalization through Presidential Regulation No. 58 of 2023. Using theoretical content analysis of policy documents and secondary data on freedom of religion or belief (2023–2024), the study argues that the primary challenge lies not in weak legal or bureaucratic instruments but in the absence of an organic social foundation that enables moderation values ​​to become part of everyday life. The analysis identifies three sources of bureaucratic plausibility fragility: dependence on political and budget cycles, the distance between policymakers and local communities, and limited intersubjective contact spaces. The study contributes by proposing four practical pillars for reconstructing an organic-cultural plausibility structure involving policymakers, educational institutions, and civil society, while recommending longitudinal research to examine the long-term sustainability and effectiveness of these strategies.